Enhanced Efficacy of Sublingual Immunotherapy in Childhood Allergic Asthma by Probiotics - Endaryanto, Anang; Irmawati, Mira (Folia Medica Indonesiana, 2018)
It is expected that probiotics may act synergistically to improve the clinical efficacy of sublingual immunotherapy (SLIT). The aim of this study was to investigate the role of probiotics in enhancing efficacy of sublingual immunotherapy in childhood allergic asthma. This was a randomized single blind clinical trial conducted on 6-17 year-old asthmatic children sensitive to house dust mite allergens. Subjects were allocated to Group A receiving SLIT, Group B receiving probiotics and SLIT, Group C receiving probiotics only. Clinical parameters (FEV1 reversibility, medication score, and symptom score) and immunological parameters (total IgE, eosinophil count, IFN-Î³, IL-2, IL-4, IL5, IL10, and TGF-b were evaluated in week 0 until 14. Statistical analysis revealed that the difference of clinical parameters (FEV1 reversibility, medication score, and symptom score) between groups were not significant. The difference of the immunological parameters of total IgE, IFN-Î³, IL-2, IL-4, IL5, IL10, and TGF-íŸ were also not significant. Eosinophil count decreased in subjects who received combination SLIT with probiotics. In conclusion, probiotics enhanced the efficacy of sublingual immunotherapy in childhood allergic asthma by decreasing the eosinophil count.